Clutter, Chaos, and Overconsumption: The Role of Mind-Set in Stressful and Chaotic Food Environments. (February 2017) - Vartanian, Lenny R.; Kernan, Kristin M.; Wansink, Brian
How do cluttered, chaotic environments—such as messy kitchens—influence snacking behavior? How does one's mind-set help prevent unwanted snacking from occurring? One hundred one female undergraduate students participated under standard-kitchen conditions or in a chaotic-kitchen condition. Participants were also asked to recall and write about a time when they felt particularly in control or particularly out of control. Finally, participants were given cookies, crackers, and carrots to taste and rate. Participants in the chaotic-kitchen condition and the out-of-control mind-set condition consumed more cookies (103 kcal) than did participants who were in the in-control mind-set condition (38 kcal). The chaotic environment had no impact on consumption of crackers or carrots. Although a chaotic environment can create a vulnerability to making unhealthy food choices, one's mind-set in that environment can either trigger or buffer against that vulnerability.